Correlation between genomic analyses with metatranscriptomic study reveals various functional pathways of Clostridium sartagoforme AAU1, a buffalo rumen isolate. Issue 1 (1st January 2016) - Nathani, Neelam M.; Duggirala, Srinivas M.; Bhatt, Vaibhav D.; Patel, Amrutlal K; Kothari, Ramesh K.; Joshi, Chaitanya G.
ABSTRACT: The present study describes the isolation and pheno-genotypic analysis of anaerobic Clostridium sartagoforme strain AAU1 from buffalo rumen, having major role in cellulose and chitin degradation. The isolate was cultured between 37°C and 42°C (optimum 40°C) temperature with an optimum pH of 7.5 in Hungate's medium supplemented with cellulose. Whole genome sequencing was performed using ion torrent PGM platforms. Local BLAST showed highest phylogenetic relation with C. sartagoforme DSM 1292 strain based on comparison of the 16S rDNA sequences. Comparison of sequences coding for housekeeping genes phosphoglycerate kinase ( pgk ) and gyrase B ( gyr B) confirmed its taxonomic position within Clostridium genus. The fermentation ability analysed biochemically using AN-Biolog plate showed that the strain utilized more than 30 different substrates as metabolite precursors. Pathway analysis based on Rapid Annotation using Subsystem Technology reveals the organism to be highly active in the production of volatile fatty acids (VFAs). Genomic analysis confirmed the role of bacteria in determining ruminant host physiology. VFAs produced by the isolate play a prominent role in animal health maintenance by contributing a major proportion of the ruminants' daily energy requirement. A deeper understanding of enzymes encoded allows further industrial applications and modulation of the rumen for enhanced farming applications.